DRAFT MODEL MONITORING AND COLLECTIONMINIMIZE EFFORTS IN POTENTIAL LOSS ACCEPTANCE OF DUTY ACQUISITION OF LANDAND BUILDING ( BPHTB ) AS A REGIONAL TAXDISTRICT KETAPANG ( AFTER LAW ENFORCEMENTNUMBER 28 OF 2009 ) - B61110054, IWAN KUSNADI (Jurnal Ekonomi Daerah (JEDA), 2015)
This study aims to determine the potential loss BPHTB, to know what efforts can be done by the district ketapan in optimizing BPHTB, as well as to determine the design of the monitoring and collection of models in an effort to minimize potential losses BPHTB. The method used in this research is